Estrogen inhibits autophagy and promotes growth of endometrial cancer by promoting glutamine metabolism - Zhou, Wen-Jie; Zhang, Jie; Yang, Hui-Li; Wu, Ke; Xie, Feng; Wu, Jiang-Nan; Wang, Yan; Yao, Li; Zhuang, Yan; Xiang, Jiang-Dong; Zhang, Ai-Jun; He, Yin-Yan; et al. (Cell communication and signaling, 2019)
Excessive estrogen exposure is an important pathogenic factor in uterine endometrial cancer (UEC). Recent studies have reported the metabolic properties can influence the progression of UEC. However, the underlying mechanisms have not been fully elucidated. Glutaminase (GLS), MYC and autophagy levels were detected. The biological functions of estrogen-MYC-GLS in UEC cells (UECC) were investigated both in vivo and in vitro. Our study showed that estrogen remarkably increased GLS level through up-regulating c-Myc, and enhanced glutamine (Gln) metabolism in estrogen-sensitive UEC cell (UECC), whereas fulvestrant (an ER inhibitor antagonist) could reverse these effects. Estrogen remarkably promoted cell viability and inhibited autophagy of estrogen sensitive UECC. However, CB-839, a potent selective oral bioavailable inhibitor of both splice variants of GLS, negatively regulated Gln metabolism, and inhibited the effects of Gln and estrogen on UECC's growth and autophagy in vitro and / or in vivo. CB-839 triggers autophagy and restricts growth of UEC by suppressing ER/Gln metabolism, which provides new insights into the potential value of CB-839 in clinical treatment of estrogen-related UEC.